2014
DOI: 10.1186/s13023-014-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical multisensory integration in Niemann-Pick type C disease – towards potential biomarkers

Abstract: BackgroundNiemann-Pick type C (NPC) is an autosomal recessive disease in which cholesterol and glycosphingolipids accumulate in lysosomes due to aberrant cell-transport mechanisms. It is characterized by progressive and ultimately terminal neurological disease, but both pre-clinical studies and direct human trials are underway to test the safety and efficacy of cholesterol clearing compounds, with good success already observed in animal models. Key to assessing the effectiveness of interventions in patients, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…These speeded responses to all four VS conditions, indicative of the so-called RSE, also violated the race model. That is, these violations confirmed that the RSE could not be accounted for by simple probability summation, consistent with previous work using other sensory pairings ( Molholm et al, 2002 ; Murray et al, 2005 ; Brandwein et al, 2011 , 2013 ; Girard et al, 2011 ; Mahoney et al, 2011 ; Megevand et al, 2013 ; Andrade et al, 2014 ). Thus, the current behavioral results suggest that visual and somatosensory neural responses interacted to produce significant RT facilitation, regardless of spatial alignment.…”
Section: Discussionsupporting
confidence: 90%
“…These speeded responses to all four VS conditions, indicative of the so-called RSE, also violated the race model. That is, these violations confirmed that the RSE could not be accounted for by simple probability summation, consistent with previous work using other sensory pairings ( Molholm et al, 2002 ; Murray et al, 2005 ; Brandwein et al, 2011 , 2013 ; Girard et al, 2011 ; Mahoney et al, 2011 ; Megevand et al, 2013 ; Andrade et al, 2014 ). Thus, the current behavioral results suggest that visual and somatosensory neural responses interacted to produce significant RT facilitation, regardless of spatial alignment.…”
Section: Discussionsupporting
confidence: 90%
“…The rationale for undertaking this study was grounded on accumulating evidence that there is severe neuronal and glial damage in thalamocortical areas of Npc1 −/− mice [ 15 , 47 ], as well as defective myelin formation and maintenance associated with Npc1 functional deficiency [ 46 , 48 ]. These abnormalities are likely associated with an impairment of various sensory pathways, as already indicated by the deficit of auditory [ 11 , 49 ] and olfactory [ 50 ] systems in Npc1 −/− mice and of multisensory processing in NPC patients [ 51 ]. As for the visual system of Npc1 −/− mice, retinal cellular and functional defects were recently described [ 19 , 20 ], but the functional integrity of their visual pathway has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Given the multiple processes that MSI must be built upon, which require long-range network integrity and functionality, it is a reasonable proposition that MSI may be particularly vulnerable to insult. Indeed, MSI has been shown to be impaired in a number of complex neurodevelopmental and neuropsychiatric disorders, such as dyslexia (Francisco, Jesse, Groen, & McQueen, 2017; Hahn, Foxe, & Molholm, 2014), schizophrenia (Ross, Saint-Amour, Leavitt, Molholm, et al, 2007) and rare lysosomal storage disorders (Andrade et al, 2014), to mention just a few. As we will elaborate below, however, it is ASD in particular that has been most extensively investigated and associated with dysfunction in MSI processing.…”
Section: Introductionmentioning
confidence: 99%